The Trust Factor: How AI Ethics and Privacy Fatigue Shape Usage Intentions for E-Commerce Users - Rifki Hanif; Hasrudy Tanjung; Halim bin Mad Lazim; Hafid Aditya Pradesa; Mime Azrina Jaafar (Image : Jurnal Riset Manajemen, 2025)
This study investigates the complex relationships between AI Ethics, Privacy Fatigue, Consumer Trust, and Usage Intention within the e-commerce sector in Malang City, Indonesia. As artifical intelligence integration rapidly grows, consumer concerns regarding algorithmic fairness and data exhaustion have become critical determinants of digital behavior and engagement. This research contributes to digital marketing theory by uniquely identifying privacy fatique as an independent psychological barrier that operates outside the traditional trust-adoption paradigm. Using a non-experimental cross-sectional survey design, data were collected from 210 e-commerce users. The conceptual model was evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that AI Ethics significantly and positively influences Consumer Trust, which acts as a pivotal mediator for Usage Intention. Conversely, Privacy Fatigue has a negligible effect on trust but exerts a potent direct negative impact on usage intention, acting as a significant psychological deterrent. These findings support a dual-pathway model where ethical integrity builds necessary trust, while privacy exhaustion triggers user resignation. Practically, e-commerce providers must prioritize transparency and simplify data management interfaces to mitigate fatigue.